Mediating role of entrepreneurial alertness between prior entrepreneurial exposures and entrepreneurial intentions - Anthony Ogbuinya Edigbo; Anastasia Ogbo; Chukwuemeka Christain Onwe; Anthony Igwe; Lawrence Chima Okafor (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the study is to ascertain the mediating role of entrepreneurial alertness (EA) on the prior entrepreneurial exposures (PEE) and entrepreneurial intentions (EI) relationship of fresh graduates in Nigeria. Research Design & Methods: We conducted a survey on fresh graduates in Nigeria (n = 387). The data gathered were analysed using Hayes' simultaneous entry on SPSS 23.0 and PROCESS 3. Findings: We found that PEE leads to an entrepreneurship career intention. We concluded that EA improves the PEE-EI relationship amongst fresh graduates in an emerging economy. Implications & Recommendations: The theory of EA is a good predictor of EI and a good mediator in the PEE-EI relationships, therefore further studies should consider EI models, especially those that involve EA and fresh graduates instead of students. Contribution & Value Added: We advance the understanding of PEE-EI relationship by utilizing the EA theory as a mediator while also testing this on a fresh graduate population in an emerging economy.
Keywords: M10; M19; 330; Prior Entrepreneurial Exposures; Entrepreneurial Intentions; Entrepreneurial Alertness; Emerging Economy; Nigeria; Fresh Graduates